EVALUATION OF LOW BACK PAIN IN PATIENTS WHO UNDERWENT BARIATRIC SURGERY - SANTOS,LARA GUERCIO DOS (2020)
ABSTRACT Objective Low back pain is an extremely common condition that can affect up to 84% of people at some point in life. It affects patients of both sexes, mainly between 30 and 50 years of age, and has a great impact on the quality of life, in addition to placing a significant demand on health services. Obesity is considered as an important risk factor for the development of low back pain since the change in body fat distribution causes changes in the locomotor system and especially in the spine. Methods The study makes a comparative, retrospective analysis of patients who underwent bariatric surgery through questionnaires to assess the improvement in their quality of life and low back pain. The data were submitted to a statistical analysis and the results compared to the literature data. Results As a result, there was a statistically significant improvement in quality of life in relation to weight loss; the greater the weight reduction, the better the quality of life and the younger the patient, the better their quality of life. Conclusions When asked about low back pain, 70.7% of patients classified it as moderate to severe. Level of evidence III; Comparative retrospective.